World Federation of Acupuncture-Moxibustion Societies (WFAS) Technical Benchmark of Acupuncture and Moxibustion: Cupping - Dan LI; Yu-Jia LI; Yi GUO; Xue ZHAO; Xiao-Dong WU; Xiao-Ning YUAN; Ono YASUO; Jia-Yin ZHANG; Yu-Fan ZHOU; Yi YANG; Tian-Yi ZHAO; Bo CHEN; et al. (World Journal of Acupuncture - Moxibustion)
World Federation of Acupuncture-Moxibustion Societies (WFAS) Technical Benchmark of Acupuncture and Moxibustion: Cupping, developed under the leadership of Tianjin University of Traditional Chinese Medicine, was approved by WFAS. This technical benchmark was issued on October 9, 2023, and implemented on December 31, 2023. The main contents include the scope, normative references, terms and definitions, procedures and rules, and safety. This article focuses on the above contents, an outlook on the application, popularization, and update plan of this technical benchmark is proposed.